Implementation of Religious Values for the Character of Students of MAN 1 Bandar Lampung - Labib, Arfani; Syafe'i, Imam; Septuri, Septuri (Journal Corner of Education, Linguistics, and Literature, 2024)
A nation that with a strong character will be able to reach the pinnacle of world civilization. The formation of national character can be done through educational institutions, both formal and non-formal. This study aims to analyze and find the form and practice of students' religious values at MAN 1 Bandar Lampung. The method used in this study is a qualitative research method with data analysis techniques used, namely data collection, data reduction, data presentation, and drawing conclusions and verification. The results of this study state that religious values ​​are implemented in the formation of the spiritual character of students at MAN 1 Bandar Lampung. The implementation of religious values ​​in MAN 1 Bandar Lampung related to religious character is Tawakal, Syukur, Polite, and Sabar.